Antioxidant Enzymes and Growth of Broiler Fed Microparticle Protein Diet with Inulin or Lactobacillus acidophillus Supplementation - N. Suthama; B. Sukamto; I. Mangisah; L. Krismiyanto (Tropical Animal Science Journal, 2023)
The effect of dahlia tuber extract or Lactobacillus acidophilus inclusion on intestinal physiology, antioxidant enzymes, and growth performance of broiler chicken given a microparticle protein-composed diet was evaluated in the present study. Three dietary treatments were applied, Control: 21% intact protein diet without additive, MP-DTE: 21% microparticle protein diet + 1.2% dahlia tuber extract as inulin source, and MP-La: 21% microparticle protein diet + 1.2 mL L. acidophilus (1 mL L. acidophilus/La equal to 108 cfu). Microparticle proteins were obtained from common protein source ingredients for poultry, fish meal, and soybean meal. A completely randomized design was assigned with 3 treatments and replicated 8 times, 10 broilers in each replication. Experimental animals were 240 broilers for treatment and 10 birds for endogenous correction. Digestibility of protein and essential amino acids, villi height, intestinal bacterial counts (LAB and Eschericia coli), short chain fatty acids/SCFA (acetate, propionate, and butyrate), antioxidant enzymes (GSH-Px and SOD), and growth performances (meat protein/MPM and fat mass/MFM, feed consumption, body weight gain/BWG, and feed conversion ratio/FCR) were variables measured. Data were statistically processed based on analysis of variance and continued to the Duncan test (p<0.05). Supplementation of dahlia inulin extract or L. acidophilus to the micropaticle protein diet significantly (p<0.05) increased N retention, villi height, LAB population, SCFA, antioxidant enzymes, and improved MPM and BWG, but decreased E. coli count, MFM, and FCR. However, feed consumption was not affected by any treatment. It can be concluded that L. acidophilus supplementation to the microparticle protein diet (MP-La) improves antioxidant enzymes, and growth performance with high meat protein and low fat mass.